Optimasi Metode Pemeriksaan HbA1c Secara Elektrokimia Berbasis Screen Printed Carbon Electrode - Furqon, Ayi; Kania, Prina Puspa (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
The quantification of HbA1c as an analyte used to monitor the success of diabetes treatment is generally examined in a laboratory with sophisticated technological equipment and professional staff. Point of care testing (POCT) is generally designed for practical examination at the patient's side. POCT HbA1c uses a screen-printed electrode (SPCE) reagent strip labeled with aptamer molecular imprinted polymer (MIP), boronate, or anti-HbA1c antibody and then quantified electrochemically. The linearity of the measurement works at a normal detection concentration of 5.5-8.5% but has not been tested at high critical concentrations. The purpose of this study was to optimize the electrochemical quantification method of HbA1c. The research procedure, SPCE was first activated with 0.1 M NaOH by cyclic voltammetry. Aptamer labeling (Fe3O4@MIPHbA1c) was carried out using the chronoamperometric technique and quantification was determined by the differential pulse voltammetry (DPV) technique. HbA1c stock of 6% and 10% in PBS pH 7.4 was used as normal and pathological concentration solution in accuracy and precision study (target quality CV <3%). The result, the average normal concentration of HbA1c was 5.9% ± 0.1%, CV=1.69% and pathological concentration was 10.4% ± 0.21%, CV=1.92%. The linearity test result of measurement ranged from 2%-15% R2=0.987. In conclusion, MIPHbA1c-activated SPCE showed optimal condition in HbA1c measurement in the normal and pathological range. Keywords: SPCE, HbA1c POCT, HbA1c Magnetit, HbA1c Aptamer